2021
DOI: 10.3389/fonc.2021.737283
|View full text |Cite
|
Sign up to set email alerts
|

Gustave Roussy Immune Score as a Novel Prognostic Scoring System for Colorectal Cancer Patients: A Propensity Score Matching Analysis

Abstract: AimThe Gustave Roussy Immune Score (GRIm-Score) was originally designed to select cancer patients for immunotherapy, and later was reported to be a novel prognostic scoring system in lung cancer and esophageal cancer. This study was aimed to determine the prognostic role and predictive performance of GRIm-Score in colorectal cancer (CRC) CRC patients.MethodsWe conducted a single-institution study of 1,579 adult CRC patients receiving surgical removal, and those patients were divided into low GRIm-Score group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Similar to our study, most of these scores were developed in the basket immunotherapy cohorts and incorporated complete blood count and biochemistry parameters into the scoring systems; however, dynamic changes in the laboratory parameters are absent in these scores [ 30 , 32 , 38 , 39 ]. The most thoroughly investigated of these scores are the GRS and RMH scores [ 31 , 40 , 41 ]. Both scores include the baseline LDH (normal vs. ≥ULN) and albumin levels (3.5 g/dL vs. <3.5 g/dL), while the baseline NLR levels and number of metastatic sites were used in the GRS [ 30 ] and RMH scores [ 31 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, most of these scores were developed in the basket immunotherapy cohorts and incorporated complete blood count and biochemistry parameters into the scoring systems; however, dynamic changes in the laboratory parameters are absent in these scores [ 30 , 32 , 38 , 39 ]. The most thoroughly investigated of these scores are the GRS and RMH scores [ 31 , 40 , 41 ]. Both scores include the baseline LDH (normal vs. ≥ULN) and albumin levels (3.5 g/dL vs. <3.5 g/dL), while the baseline NLR levels and number of metastatic sites were used in the GRS [ 30 ] and RMH scores [ 31 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The three components of the score (NLR, LDH, and albumin) re ect patients' nutritional status, systemic in ammation, and immune status [13]. Previous studies have reported that GRIm score correlated with tumor stage, tumor size, BMI, and performance status [15,16,20]. In the present study, GRIm score was closely correlated with patient characteristics and tumor conditions, including advanced age, comorbidities, and T/N/M status, in agreement with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…GRIm score has reported as a prognostic factor for various cancers [14][15][16]. Feng and colleagues examined the prognostic value of GRIm score in esophageal cancer [14], and found that patients with high GRIm had poor CSS compared to those with low GRIm (10.3% vs. 35.0%, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations